Is Social Housing Affordable? - Tuukka Saarimaa; Essi Eerola (European Regional Science Association (ERSA), 2013)
Supply subsidies to owners of rental housing construction are typically aimed at increasing the overall size of the housing stock or at guaranteeing affordable housing for low-income households. This paper studies whether and how much the tenants of social housing units benefit from this subsidy. We use on free market rental units and subsidized rental units owned by the city of Helsinki. Our data contain detailed information about the characteristics of the units, including their location. We employ hedonic regression methods to predict rents for the subsidized units and use the results to calculate the subsidy the tenants obtain when occupying a subsidized unit instead of an otherwise similar free market rental unit. We find that on average the monthly subsidy per unit is 246 Euros, whereas the average monthly subsidy per unit?s square meters is 3.88 Euros. We also find that there is substantial heterogeneity in the amount of subsidy that different subsidized units receive.
Keywords: 330; Housing supply subsidies; Social housing; Hedonic regression